The Oxford handbook of international law in Asia and the Pacific - Chesterman, Simon; Owada, Hisashi; Saul, Ben (Oxford handbooks., 2019)
The growing economic and political significance of Asia has exposed a tension in the modern international order. Despite growing in power and influence, Asian states traditionally played a minimal role in creating the norms and institutions of international law. They were the least likely to be parties to international agreements or be represented in international organizations. That is changing. Today, there is widespread scholarly and practitioner interest in international law in the Asia-Pacific region, as well as developments in the practice of states. The change has been driven by threats as well as opportunities. On the threat side are transnational challenges such as climate change, in which the involvement of Asian states is essential, and occasional flashpoints such as the territorial disputes of the South China and the East China Seas. In terms of opportunities, economic integration and the proliferation of dispute settlement mechanisms have encouraged greater domestic implementation of international norms across Asia. These evolutions join a more long-standing interest in parts of Asia (notably South Asia) in post-colonial theory and the history of international law. This Oxford Handbook brings together pre-eminent and emerging specialists to analyse the approach and influence of key states in the region. It also explores whether truly 'Asian' trends can be identified and what this might mean for the international order.